Cubic and hexagonal liquid crystal gels for ocular delivery with enhanced effect of pilocarpine nitrate on anti-glaucoma treatment - Wang Xingqi; Zhang Yong; Li Xing; Wang Yang; Huang Jie; Hu Rongfeng; Gui Shuangying; Chu Xiaoqin (Taylor & Francis Group, 2019)
The objective of this work was to investigate phytantriol-based liquid crystal (LC) gels including cubic (Q2) and hexagonal (H2) phase for ocular delivery of pilocarpine nitrate (PN) to treat glaucoma. The gels were produced by a vortex method and confirmed by crossed polarized light microscopy, small-angle X-ray scattering, and rheological measurements. Moreover, the release behaviors and permeation results of PN from the gels were estimated using in vitro studies. Finally, the anti-glaucoma effect of LC gels was evaluated by in vivo animal experiments. The inner structure of the gels was Pn3m-type Q2 and H2 phase, and both of them showed pseudoplastic fluid properties based on characterization techniques. In vitro release profiles suggested that PN could be sustainably released from LC gels within 48 h. Compared with eye drops, Q2 and H2 gel produces a 5.25-fold and 6.23-fold increase in the Papp value (p < .05), respectively, leading to a significant enhancement of corneal penetration. Furthermore, a good biocompatibility and longer residence time on precorneal for LC gels confirmed by in vivo animal experiment. Pharmacokinetic studies showed that LC gels could maintain PN concentration in aqueous humor for at least 12 h after administration and remarkably improve the bioavailability of drug. Additionally, in vivo pharmacodynamics studies indicated that LC gels had a more significant intraocular pressure-lowering and miotic effect compared to eye drops. These research findings hinted that LC gels would be a promising pharmaceutical strategy for ocular application to enhance the efficacy of anti-glaucoma.